DIGITAL LEADERSHIP IN PESANTREN: BRIDGING TECHNOLOGICAL AFFORDANCES FOR SUSTAINABLE DISTANCE EDUCATION ECOSYSTEMS - Moh. Ali; Imron Imron; Al Ghazali; Alwi Husein Prawinegoro; Neila Najmi Aulia (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study analyzes and describe the practices of Kiai's digital leadership in implementing distance education in pesantren, particularly in bridging the gap between technological affordances and a sustainable educational ecosystem. The research employed a qualitative approach with a multi-case study design across four pesantren representing different typologies (modern, salaf, and hybrid). Data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted using an a semantic analysis, while triangulation was applied through source triangulation to ensure validity. The findings revealed four main digital leadership strategies: role modeling, delegation of authority, normative-restrictive control through religious legitimacy, and incremental-institutional approaches. These strategies demonstrated that the success of distance education in pesantren is highly dependent on the Kiai’s ability to integrate technology with institutional values and cultural contexts. The study implied that value-based digital leadership plays a crucial role in ensuring sustainable digital transformation in religious educational institutions, offering both theoretical contributions to digital leadership discourse and practical guidance for pesantren management.